Faith in search of certainty: Karl Barth's method in dogmatics and apologetics. A study in historical theology and cultural history - Haupert, Thomas J. (The University of Edinburgh, 1977)
She thesis seeks to examine Karl Earth's theo logical method against the backdrop of the historical context in which it developed, that is, the politicalsocial-econonic context, and the philosophical-theological context.

After outlining this context, and tracing Earth's theological development up to 1930 in Part I, the thesis turns its attention to Earth's study of Anselra'e theological method, the Fides -uaerens Intellectual of 1931. here, prior to the commencement of his Church Dogmatics, both Earth himself, and his major interpreters (after I960), concur that Earth "found himself" methodologically. Thus Part II of the thesis seeks to examine both (1) the accuracy of Earth's interpretation of Arise 1m and (2) the nature of the theological method Earth attributes to Anselra, The thesis maintains that Earth "found himself" methodologically only by seriously misinterpreting Ansel® at a quite basic level.

Part III of the thesis seeks to examine several basal aspects of the actual method of Earth's theology. As 'the Credo', or the credal tradition and dogmas of the Early Church, was of central importance to the method Earth attributed to Ansel® (in contrast to cripture), Part III asks questions as to the place, importance and type of relation to Tradition, specificx 4 ally the credal Tradition of the Early Church, in Barth's theology# This aspect of Earth's laethod has been all but ignored by the major interpreters of Barth, Among our findings are that (1) credal beliefs form a significant portion of the basis upon which this theology is built; (2) the type of relation to credal Tradition is characterized by unquestioning submission to, and dogmatic assertion of these credal beliefs. In addition, there is significant evidence that Barth operates on the assumption that credal Tradition is an infallible articulation of revelation, and an infallible form of "the Word of God."

Part III goes on to examine issues of method concerning the relationships between man, ti:oology and revelation. Here the thesis finds that unquestioning submission to Tradition is accompanied by unquestioning submission to what is alleged to be revelation, that is, to what is experienced as "the Word of God" in an "EVent" in which human words (allegedly) become "the Word of God" by the action of the deity (the human words of Boripture, etc.)

Evidence is also found that Barth operates upon the assumption that Dogmatics itself, like Scripture, preaching (and creeds) is, at least at points, a human form of "the Word of God," It is from this vantage point that Barth's conception of Apologetics is viewed. It is a conception in which the deity allegedly 'validates' the theologians own words as "the Word of God" for "unbelievers".

After laying out and examining these several . basal aspects of Garth's method, the thesis seeks to put t is ethod into historical perspective, viewing it firstly with reference to the development of another influential figure, the composer, Igor Stravinsky; and secondly, by seeking possible reasons for the develop e it of Garth*s method by turning to consider the extremely troubled economic, social and political context In W'.ic.i this ...ethod developed.

The thesis concludes by summarizing the results of research, and by listing eight reasons for holding that Earth's theological programme should not be t a en seriously as a real option for theology. In a concludiing critique Earth's theology is found to nave only minimal relevance for preaching, that is specifically for Earth's own preaching. Thus Earth theology apparently has only minimal relevance for its most central aim: to serve the preaching of 'the Church'.